Oleanolic Acid Induces the Type III Secretion System of Ralstonia solanacearum - Wu, Dousheng; Ding, Wei; Zhang, Yong; Liu, Xuejiao; Yang, Liang (Frontiers in Microbiology, 2015)
Ralstonia solanacearum, the causal agent of bacterial wilt, can naturally infect a wide range of host plants. The type III secretion system (T3SS) is a major virulence determinant in this bacterium. Studies have shown that plant derived compounds are able to inhibit or induce the T3SS in some plant pathogenic bacteria, though no specific T3SS inhibitor or inducer has yet been identified in R. solanacearum. In this study, a total of 50 different compounds were screened and almost half of them (22 of 50) significantly inhibited or induced the T3SS expression of R. solanacearum. Based on the strong induction activity on T3SS, the T3SS inducer oleanolic acid (OA) was chosen for further study. We found that OA induced the expression of T3SS through the HrpG-HrpB pathway. Some type III effector genes were induced in T3SS inducing medium supplemented with OA. In addition, OA targeted only the T3SS and did not affect other virulence determinants. Finally, we observed that induction of T3SS by OA accelerated disease progress on tobacco. Overall our results suggest that plant-derived compounds are an abundant source of R. solanacearum T3SS regulators, which could prove useful as tools to interrogate the regulation of this key virulence pathway.